The Reality of Social Interaction among Najran University Students and Ways to Enhance it in the University Learning Environment - Nimer , Ameen (Dirasat: Educational Sciences, 2020)
The study aimed to identify the situation of social interaction among Najran University students from students’ perspectives. The sample of the study (N=629 male and female students) was selected from the colleges of Humanities and Science. To achieve this objective, a questionnaire of (21) items was classified in three sections that measured the aspects of interaction between the students, and the students and the faculty members. On the other hand, as well as between students and the extent of their interaction with the university’s activities. The researcher utilized the descriptive analytical approach. The findings of the study revealed the situation of social interaction among Najran University students from students’ perspectives, whose mean score (M=1.71) on a 3 point- Likert scale. The results also showed that there are statistically significant differences at the level of (α = 0.05) at the first domain in favor of scientific colleges, and there were no statistically significant differences on the total score and on both the second and third domains. The results also showed statistically significant differences at the level of α (0.05 = 0.05) on the total score and on the first domain in favor of females, while there were no statistically significant differences at (α = 0.05) at the second and third domains. The study recommended the university provide an environment based on building social relationships between its various parties, and for the faculty members have the largest role in provide opportunities that help in creating positive social interaction.